Informal and formal mental health: preliminary qualitative findings - O'Neill, Linda; George, Serena; Koehn, Corinne; Shepard, Blythe (Co-Action Publishing, 2013)
Sherpa Romeo green journal Background. Northern-based research on mental health support, no matter the specific profession, helps to inform instruction of new practitioners and practitioners already working in rural or isolated conditions. Understanding the complexities of northern mental health support not only benefits clients and practitioners living in the North, but also helps prepare psychologists and counsellors preparing to work in other countries with large rural and isolated populations. The qualitative phase is part of a multi-year research study on informal and formal mental health support in northern Canada involving the use of qualitative and quantitative data collection and analysis methods. Objective. The main objective of the qualitative phase interviews was to document in-depth the situation of formal and informal helpers in providing mental health support in isolated northern communities in northern British Columbia, northern Alberta, Yukon and Northwest Territories (NWT). The intent of in-depth interviews was to collect descriptive information on the unique working conditions of northern helping practitioners for the development of a survey and subsequent community action plans for helping practitioner support. Design. Twenty participants in northern BC, Yukon and NWT participated in narrative interviews. Consensual qualitative research (CQR) was used in the analysis completed by 7 researchers. The principal researcher and research associate then worked through all 7 analyses, defining common categories and themes, and using selections from each researcher in order to ensure that everyone’s analysis was represented in the final consensual summary. Results. The preliminary results include 7 main categories consisting of various themes. Defining elements of northern practice included the need for generalist knowledge and cultural sensitivity. The task of working with and negotiating membership in community was identified as essential for northern mental health support. The need for revised ...